2006
DOI: 10.4314/sinet.v28i2.18245
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil carbon and total nitrogen following reforestation of previously cultivated land in the highlands of Ethiopia

Abstract: Changes in soil C and total N stocks were investigated following reforestation of previously cultivated soil in compariso n with soil subjected to continuous cultivation and soil under an adjacent natural forests in south central highlands of Ethiopia. Two of the most widely planted tree species in the highlands of Ethiopia, namely Eucalyptus saligna and Cupressus lusitanica, were considered in the plantation treatments. Soil C and total N contents in the upper 0-10 and 10-20 cm soil layers were significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…Due to the reduction in aboveground biomass through different impacts from human and livestock activities; there will be variation in SOC accumulation and TN across the fragments sampled with relatively higher concentration for fragments with higher diversity of species. The loss of SOC and TN is particularly significant in the context of land use changes due to the reduction in aboveground biomass (Lemenih et al 2005;Gelaw et al 2013;Gurmessa et al 2016;Tesfaye et al 2016). We also anticipate a decrease in SOC and TN as depth increases (Lemenih et al 2005).…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Due to the reduction in aboveground biomass through different impacts from human and livestock activities; there will be variation in SOC accumulation and TN across the fragments sampled with relatively higher concentration for fragments with higher diversity of species. The loss of SOC and TN is particularly significant in the context of land use changes due to the reduction in aboveground biomass (Lemenih et al 2005;Gelaw et al 2013;Gurmessa et al 2016;Tesfaye et al 2016). We also anticipate a decrease in SOC and TN as depth increases (Lemenih et al 2005).…”
Section: Introductionmentioning
confidence: 71%
“…Maintaining SOC and TN through improvements of forest cover is an important aspect in climate change mitigation as the loss of carbon and nitrogen to the atmosphere through soil disturbances can cause an enormous addition of the elements to the atmosphere (Lemenih et al 2005;Vágen et al 2005;Strassburg et al 2010;Gamfeldt et al 2013;Berenguer et al 2014;Gelaw et al 2014;Gurmessa et al 2016;Tesfaye et al 2016). It has been found that forests and their soils store about 45% of the terrestrial carbon and act as crucial carbon sources (Gamfeldt et al 2013;Tesfaye et al 2016), and tropical forest ecosystem soils store about 60% of the total carbon stocks (Vágen et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There exist several published scientific articles and case studies on soil carbon pools for different parts of Ethiopia (Yimer et al 2006;Girmay et al 2008;Hawando 1997;Solomon et al 2002a;Lemenih et al 2005;Haileslassie et al 2005;Lemma et al 2006;Edwards 2007;Chibsa and Ta 2009;Freier et al 2009;Fisseha et al 2011;Kim et al 2015;Demessie et al 2015;Berihu et al 2017) but with a missing gap on the national soil database carbon pools estimate (Shiferaw et al 2013;Okolo et al 2016). However, most of the SOC researches were conducted in the southern part of Ethiopia, thus not giving a comprehensive clear overview of the trend in total soil carbon distribution data across different landscapes and regions of Ethiopia, which this review intends to address systematically.…”
Section: Past and Present Scientific Evidence Of Soil Organic Carbon mentioning
confidence: 99%
“…However, most of the SOC researches were conducted in the southern part of Ethiopia, thus not giving a comprehensive clear overview of the trend in total soil carbon distribution data across different landscapes and regions of Ethiopia, which this review intends to address systematically. For example in the highlands of southern Ethiopia, changes in SOC stock was investigated by Lemenih et al (2005) after reforestation of previously cultivated soil in comparison with continuously cultivated soils and adjacent natural forests soils. For Cupressus lusitanica and Eucalyptus saligna, they reported an average annual soil C accumulation estimate of 156 and 37 g C m −2 year −1 respectively.…”
Section: Past and Present Scientific Evidence Of Soil Organic Carbon mentioning
confidence: 99%